A new modified schedule of Sunitinib for metastatic renal cell carcinoma: a retrospective analysis - Buti, S.; Donini, M.; Lazzarelli, et al., S. (Acta Biomedica Atenei Parmensis, 2012)
Background and aim of the work: Sunitinib 50 mg/day given for 4 weeks followed by 2 weeks off treatment (4+2 schedule) is a standard treatment for metastatic renal cell carcinoma, but several patients are forced to reduce the doses and/or had to discontinue therapy permanently due to toxicity. Recent data showed that increased exposure to sunitinib is associated with improved clinical outcome underlining the key role of dose-intensity in the efficacy/toxicity balance.We investigated the tolerability and efficacy of a modified schedule. Patients and methods: This is a retrospective analysis which assessed consecutive non-progressive metastatic renal cell carcinoma patients admitted to our hospital who had at least a grade 2 toxicity during sunitinib therapy, and then switched to a modified schedule maintaining the same dose-intensity of 4+2 schedule: starting on Monday, 1 tablet/day for 5 consecutive days a week (days 6 and 7 off therapy) for 5 weeks and 1 tablet/day on days 1, 3 and 5 in the sixth week (days 2, 4, 6 and 7 off therapy) until disease progression. Primary end points were toxicity changes assessment and schedule feasibility. Results: Complete data from eight nephrectomized patients were collected: 6 males; median age 61; 3 pretreated patient. Median time from start therapy to switch was 7.4 months. After switch, treatment delays and dose reductions decreased from 50% to 25% and from 37% to 12% of patients respectively. Toxicity was reduced. Conclusions: Even though no conclusions can be drawn about the actual effectiveness and toxicity of our schedule compared to the standard dosing schedule, it seems to be well tolerated and able to maintain a high adherence to therapy, resulting in maintenance of antitumour activity. This new modified schedule requires and deserves further studies.